New Vaccine Formulations Containing a Modified Version of the Amastigote 2 Antigen and the Non-Virulent Trypanosoma cruzi CL-14 Strain Are Highly Antigenic and Protective against Leishmania infantum Challenge - Almeida, Ana Paula M. M.; Machado, Leopoldo F. M.; Doro, Daniel; Nascimento, Frederico C.; Damasceno, Leonardo; Gazzinelli, Ricardo Tostes; Fernandes, Ana Paula; Junqueira, Caroline (Frontiers in Immunology, 2018)
Visceral leishmaniasis (VL) is a major public health issue reported as the second illness in mortality among all tropical diseases. Clinical trials have shown that protection against VL is associated with robust T cell responses, especially those producing IFN-γ. The Leishmania amastigote 2 (A2) protein has been repeatedly described as immunogenic and protective against VL in different animal models; it is recognized by human T cells, and it is also commercially available in a vaccine formulation containing saponin against canine VL. Moving toward a more appropriate formulation for human vaccination, here, we tested a new optimized version of the recombinant protein (rA2), designed for Escherichia coli expression, in combination with adjuvants that have been approved for human use. Moreover, aiming at improving the cellular immune response triggered by rA2, we generated a recombinant live vaccine vector using Trypanosoma cruzi CL-14 non-virulent strain, named CL-14 A2. Mice immunized with respective rA2, adsorbed in Alum/CpG B297, a TLR9 agonist recognized by mice and human homologs, or with the recombinant CL-14 A2 parasites through homologous prime-boost protocol, were evaluated for antigen-specific immune responses and protection against Leishmania infantum promastigote challenge. Immunization with the new rA2/Alum/CpG formulations and CL-14 A2 transgenic vectors elicited stronger cellular immune responses than control groups, as shown by increased levels of IFN-γ, conferring protection against L. infantum challenge. Interestingly, the use of the wild-type CL-14 alone was enough to boost immunity and confer protection, confirming the previously reported immunogenic potential of this strain. Together, these results support the success of both the newly designed rA2 antigen and the ability of T. cruzi CL-14 to induce strong T cell-mediated immune responses against VL in animal models when used as a live vaccine vector. In conclusion, the vaccination strategies explored here reveal promising alternatives for the development of new rA2 vaccine formulations to be translated human clinical trials.